Composition for polyvinyl chloride waterproofing roll, polyvinyl chloride waterproofing roll and preparation method and application thereof

By using a combination of polyvinyl chloride and ethylene-vinyl acetate-carbon monoxide copolymer, combined with kneading, extrusion plasticization, calendering and radiative crosslinking, polyvinyl chloride with dual functions of waterproofing and thermal insulation was prepared by combining the processes of kneading, extrusion plasticization, calendering and radiative crosslinking. The waterproof coil material solves the problems of complex construction, high cost and difficult maintenance in the existing technology, and achieves efficient, economical and reliable roof waterproofing construction.

CN118620336BActive Publication Date: 2025-02-25JINGMEN KESHUN NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202410645494.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-02-25
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The existing polyvinyl chloride waterproof coils are difficult to take into account both waterproof and thermal insulation properties, resulting in complex construction, high cost and difficult maintenance.

Method used

Compositions composed of polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, filler, expandable microspheres, crosslinking agents, antioxidants, etc. are used to plasticize, calender and shaping by kneading, extrusion and plasticizing, and calendering. The process of radiation crosslinking is used to prepare polyvinyl chloride waterproof coils.

Benefits of technology

The prepared polyvinyl chloride waterproof coil has low hardness and high toughness. It can be closed independently of the air holes after foaming, and has good waterproofing functions. It simplifies construction steps, reduces costs, and reduces maintenance frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004854708800000101
    Figure BDA0004854708800000101
  • Figure BDA0004854708800000111
    Figure BDA0004854708800000111
  • Figure BDA0004854708800000112
    Figure BDA0004854708800000112
Patent Text Reader

Abstract

The present invention relates to the technical field of waterproofing coiled materials, and discloses a composition for polyvinyl chloride waterproofing coiled materials, a polyvinyl chloride waterproofing coiled materials, and a preparation method and application thereof. The composition contains polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, a plasticizer, a filler, expandable microspheres, a crosslinking agent, and an antioxidant; relative to 100 parts by weight of polyvinyl chloride, the content of ethylene-vinyl acetate-carbon monoxide copolymer is 10-40 parts by weight, the content of the plasticizer is 35-50 parts by weight, the content of the filler is 20-55 parts by weight, the content of the expandable microspheres is 1-3 parts by weight, the content of the crosslinking agent is 1-3 parts by weight, and the content of the antioxidant is 0.1-0.4 parts by weight. The polyvinyl chloride waterproofing coiled material not only has strong tensile strength and elongation, but also has good waterproof function while being able to insulate and heat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, and in particular to a composition for polyvinyl chloride waterproof coiled materials, a polyvinyl chloride waterproof coiled material, and a preparation method and application thereof. Background Art

[0002] The existing construction scheme usually makes a thermal insulation layer on the roof structure, and a waterproof layer and a protective layer on the upper part. The polyvinyl chloride (PVC) waterproofing membrane in the prior art is mainly based on polyvinyl chloride resin, and is made by adding a series of additives and adopting advanced production technology. This kind of membrane has excellent performance in tensile strength, elongation, shrinkage and service life, stable performance and reliable quality, which brings convenience to construction. However, the main function of this membrane is limited to waterproofing, and it does not have a thermal insulation function.

[0003] In current construction practice, in order to achieve the effects of thermal insulation and waterproofing at the same time, the usual practice is to first lay a thermal insulation layer on the roof structure, and then lay a waterproof layer and a protective layer on top of it. On the one hand, this multi-layer construction method makes the entire roof structure complicated. This complex structure not only increases the construction steps and increases the difficulty of construction, but is also easily affected by natural factors (such as wind, rain, temperature, etc.) and process limitations, resulting in extended construction period and increased cost. On the other hand, since the thermal insulation layer and the waterproof layer are separate, they are prone to cross-influence. For example, the aging of the waterproof layer may affect the performance of the thermal insulation layer, and vice versa. This cross-influence is likely to lead to aging and damage of material components, thereby shortening the service life of the entire roof. Therefore, regular repairs and replacements are required, increasing the cost of later maintenance.

[0004] In addition, the materials in the prior art often lack comprehensive performance, that is, it is difficult to take into account both waterproof and heat preservation functions at the same time. This means that in practical applications, it is often necessary to select a combination of multiple materials, further increasing the complexity and cost of construction.

[0005] CN110983808A discloses an internally reinforced anti-aging polyvinyl chloride waterproofing coil and a preparation method thereof, wherein the waterproofing coil comprises a fabric inner reinforcement layer, wherein a large amount of additives are added to the anti-aging PVC waterproofing layer, and the waterproofing coil has good mechanical properties and high mechanical strength. However, the waterproofing coil has high construction cost and difficulty, and poor thermal insulation function.

[0006] CN108690290A discloses an environmentally friendly cross-linked polyvinyl chloride waterproofing membrane, which uses polyvinyl chloride as the main raw material, adds ethylene-vinyl acetate-carbon monoxide copolymer, a cross-linking agent and a calcium zinc stabilizer, etc., and also needs to add a cross-linking aid and a chemical coupling agent for high-temperature cross-linking, which increases production costs and causes environmental pollution.

[0007] To sum up, there is an urgent need to develop a new type of PVC waterproof membrane with both waterproof and thermal insulation functions to solve the problems of complex construction, high cost, and difficult later maintenance in the existing technology, and provide a more efficient, economical and reliable solution for roof waterproofing construction. Summary of the invention

[0008] The purpose of the present invention is to solve the problem that the polyvinyl chloride waterproofing membrane in the prior art is difficult to achieve both waterproofing and heat preservation performance.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for polyvinyl chloride waterproofing membrane, which contains polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, filler, expandable microspheres, crosslinking agent, antioxidant;

[0010] Relative to 100 parts by weight of the polyvinyl chloride, the content of the ethylene-vinyl acetate-carbon monoxide copolymer is 10-40 parts by weight, the content of the plasticizer is 35-50 parts by weight, the content of the filler is 20-55 parts by weight, the content of the expandable microsphere is 1-3 parts by weight, the content of the cross-linking agent is 1-3 parts by weight, and the content of the antioxidant is 0.1-0.4 parts by weight;

[0011] Wherein, the weight average molecular weight of the polyvinyl chloride is 150,000-210,000, and the average degree of polymerization is 1000-1350;

[0012] The melting point of the ethylene-vinyl acetate-carbon monoxide copolymer is 45-66°C;

[0013] The average particle diameter of the expandable microspheres is 20-50 μm.

[0014] The second aspect of the present invention provides a method for preparing a polyvinyl chloride waterproofing membrane, the method comprising: kneading, extruding and plasticizing, calendering and shaping, and irradiating and crosslinking the components in the composition for polyvinyl chloride waterproofing membrane in sequence;

[0015] The composition for polyvinyl chloride waterproof membrane is the composition described in the first aspect.

[0016] The third aspect of the present invention provides a polyvinyl chloride waterproofing membrane prepared by the method described in the second aspect.

[0017] The fourth aspect of the present invention provides application of the polyvinyl chloride waterproof membrane described in the third aspect in the field of building waterproofing.

[0018] Through the above technical solution, the present invention has at least the following advantages:

[0019] (1) The polyvinyl chloride waterproofing membrane provided by the present invention has the advantages of low hardness and high toughness.

[0020] (2) Compared with traditional PVC waterproof membranes, the method for preparing polyvinyl chloride waterproof membranes provided by the present invention has good compatibility between the components. The prepared waterproof membrane has independent pores after foaming, and the pores are closed to each other without forming water leakage channels, so that it can have good waterproof function while being able to insulate and heat.

[0021] (3) The method for preparing polyvinyl chloride waterproofing membrane provided by the present invention can reduce the amount of plasticizer added while ensuring the high toughness of the waterproofing membrane. Good toughness can significantly improve the construction performance of the membrane.

[0022] (4) The method for preparing polyvinyl chloride waterproofing membrane provided by the present invention improves the tensile strength and elongation of the prepared waterproofing membrane during foaming, thereby solving the problem of reduced mechanical strength of traditional PVC after foaming.

[0023] (5) When the polyvinyl chloride waterproofing membrane provided by the present invention is applied to the field of building waterproofing, it can not only simplify the construction steps and reduce the construction difficulty and cost, but also reduce the frequency of maintenance and replacement, thereby reducing the subsequent maintenance cost, providing a more efficient, economical and reliable solution for roof waterproofing construction. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] In the present invention, ethylene-vinyl acetate-carbon monoxide copolymer is referred to as "EVACO"; polyvinyl chloride is referred to as "PVC resin"; pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is referred to as "1010"; tris(2,4-di-tert-butylphenyl) phosphite is referred to as "168".

[0026] As mentioned above, the first aspect of the present invention provides a composition for polyvinyl chloride waterproofing membrane, the composition comprising polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, filler, expandable microspheres, crosslinking agent, antioxidant;

[0027] Relative to 100 parts by weight of the polyvinyl chloride, the content of the ethylene-vinyl acetate-carbon monoxide copolymer is 10-40 parts by weight, the content of the plasticizer is 35-50 parts by weight, the content of the filler is 20-55 parts by weight, the content of the expandable microsphere is 1-3 parts by weight, the content of the cross-linking agent is 1-3 parts by weight, and the content of the antioxidant is 0.1-0.4 parts by weight;

[0028] Wherein, the weight average molecular weight of the polyvinyl chloride is 150,000-210,000, and the average degree of polymerization is 1000-1350;

[0029] The melting point of the ethylene-vinyl acetate-carbon monoxide copolymer is 45-66°C;

[0030] The average particle diameter of the expandable microspheres is 20-50 μm.

[0031] Preferably, the melt mass flow rate of the ethylene-vinyl acetate-carbon monoxide copolymer at 190° C. and a load of 2.16 kg is 25-35 g / 10 min, and the density is 1-1.02 g / cm 3 In this preferred case, a polyvinyl chloride waterproofing membrane with better thermal insulation performance can be obtained.

[0032] Preferably, in the ethylene-vinyl acetate-carbon monoxide copolymer, the content of the vinyl acetate structural unit is 18-26 wt %.

[0033] Preferably, the glass transition temperature of the ethylene-vinyl acetate-carbon monoxide copolymer is -36°C to -32°C.

[0034] Preferably, the expandable microspheres have a core-shell structure, and the average thickness of the shell of the expandable microspheres is 5-15 μm.

[0035] Preferably, the material forming the shell of the expandable microspheres includes a thermoplastic acrylic polymer.

[0036] Preferably, the inner cavity of the core-shell structure of the expandable microsphere contains hydrocarbons.

[0037] Preferably, the thermoplastic acrylic polymer is selected from at least one of methyl acrylate-acrylonitrile copolymer, ethyl acrylate-acrylonitrile copolymer and methyl methacrylate-acrylonitrile copolymer.

[0038] Preferably, the hydrocarbon is selected from at least one of butane, isobutane and isopentane.

[0039] Preferably, the filler is selected from at least one of light calcium carbonate, titanium dioxide, heavy calcium carbonate and montmorillonite. More preferably, the filler is light calcium carbonate and / or titanium dioxide.

[0040] Preferably, the content of the light calcium carbonate is 20-50 parts by weight, and the content of the titanium dioxide is 2-4 parts by weight.

[0041] Preferably, the light calcium carbonate has a weight average diameter of 2.6-18 μm and a bulk density of 0.5-0.7 g / cm 3 In this preferred case, a polyvinyl chloride waterproofing membrane with better thermal insulation performance can be obtained.

[0042] More preferably, the light calcium carbonate has a whiteness of 92-97 wt % and a moisture content of 0.3-0.8 wt %.

[0043] It should be noted that the whiteness of the light calcium carbonate refers to the "purity relative to impurities".

[0044] Preferably, the weight average diameter of the titanium dioxide is 2-3 μm.

[0045] Preferably, the plasticizer is selected from at least one of dioctyl phthalate, dioctyl terephthalate, trioctyl trimellitate, and epoxidized soybean oil.

[0046] Preferably, the crosslinking agent is trimethylolpropane triacrylate and / or ethoxylated trimethylolpropane triacrylate.

[0047] Preferably, the antioxidant is a combination of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite in a weight ratio of 1:1-2. In this preferred embodiment, a polyvinyl chloride waterproofing membrane with better thermal insulation performance can be obtained.

[0048] Preferably, the composition further contains at least one of a calcium zinc stabilizer, a lubricant and a light stabilizer.

[0049] Preferably, relative to 100 parts by weight of the polyvinyl chloride, the content of the calcium zinc stabilizer is 2-4 parts by weight, the content of the lubricant is 0.1-1 part by weight, and the content of the light stabilizer is 0.1-1 part by weight.

[0050] Preferably, the lubricant is selected from at least one of monoglyceride, polyethylene wax, paraffin, oxidized polyethylene wax, fatty acid ester wax and metal soap.

[0051] Preferably, the light stabilizer is selected from at least one of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

[0052] As mentioned above, the second aspect of the present invention provides a method for preparing a polyvinyl chloride waterproofing membrane, the method comprising: kneading, extruding and plasticizing, calendering and shaping, and irradiating and crosslinking the components in the composition for polyvinyl chloride waterproofing membrane in sequence;

[0053] The composition for polyvinyl chloride waterproof membrane is the composition described in the first aspect.

[0054] According to a particularly preferred embodiment, the kneading operation comprises:

[0055] (S1) mixing and heating polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, filler, crosslinking agent, antioxidant, calcium zinc stabilizer, lubricant and light stabilizer components to obtain an intermediate;

[0056] (S2) Cooling the intermediate under stirring, and then contacting and mixing the obtained material with expandable microspheres to obtain a mixed material.

[0057] The present invention has no particular limitation on the equipment used for mixing heating, cooling and contact mixing. For example, a high-speed kneader can be used for the mixing heating, and a cold mixing kettle can be used for the cooling and contact mixing.

[0058] Preferably, in step (S1), the mixing and heating conditions include: an end temperature of 95-105°C, a time of 6-18 min, and a rotation speed of 100-120 rpm.

[0059] Preferably, in step (S2), the stirring speed is 40-150 rpm; the cooling end temperature is 35-40° C.; and the contact mixing time is 3-6 min.

[0060] The present invention has no particular limitation on the equipment used for extrusion plasticization. For example, the equipment used for extrusion plasticization is a parallel twin-screw extruder, the feeding speed of the parallel twin-screw extruder is 50-500rpm, and the aspect ratio is 28-50:1.

[0061] Preferably, the extrusion plasticization conditions include: a temperature of 140-180° C. and an extrusion speed of 3-6 m / min.

[0062] The present invention has no particular limitation on the equipment used for calendering and shaping. For example, a three-roll calender can be used for calendering and shaping.

[0063] Preferably, the device used for the radiation cross-linking is an electron accelerator.

[0064] Preferably, the radiation cross-linking conditions include: irradiation energy of 1-2 MeV, beam current of 10-12 mA, and irradiation dose of 100-120 kGy. In this preferred case, the solution of the present invention can make the waterproof roll material have better waterproof function and further improve its tensile strength and elongation.

[0065] As mentioned above, the third aspect of the present invention provides a polyvinyl chloride waterproofing membrane prepared by the method described in the second aspect.

[0066] As mentioned above, the fourth aspect of the present invention provides the use of the polyvinyl chloride waterproof membrane described in the third aspect in the field of building waterproofing.

[0067] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0068] PVC resin (PVC-1) was purchased from Hanwha Chemical (Ningbo) Co., Ltd. with the brand name HG-1300, a weight average molecular weight of 181,121, and an average degree of polymerization of 1,290.

[0069] PVC resin (PVC-2) was purchased from Xinjiang Tianye (Group) Co., Ltd., brand SG-3, with a weight average molecular weight of 186,805 and an average degree of polymerization of 1278.

[0070] PVC resin (PVC-3) was purchased from Tianjin LG Dagu Chemical Co., Ltd. with a brand name of SG-7, a weight average molecular weight of 132,256, and an average degree of polymerization of 825.

[0071] EVACO (Ⅰ), trade name Elvaloy, purchased from The Dow Chemical Company, USA, brand ELVALOY TM 741Copolymer; the content of vinyl acetate structural units is 16wt%, the melt mass flow rate at 190℃ and 2.16kg load is 35g / 10min, and the density is 1.0g / cm 3 , melting point is 66°C and glass transition temperature is -32°C.

[0072] EVACO (ⅠⅠ), purchased from Dow Chemical Company, USA, brand ELVALOY TM742Copolymer; the content of vinyl acetate structural units is 16wt%, the melt mass flow rate at 190℃ and 2.16kg load is 35g / 10min, and the density is 1.02g / cm 3 , melting point is 45℃, and glass transition temperature is -32℃.

[0073] EVACO (IIII), purchased from The Dow Chemical Company, USA, brand ELVALOY TM 4924Copolymer; the content of vinyl acetate structural units is 18wt%, the melt mass flow rate at 190℃ and 2.16kg load is 15g / 10min, and the density is 1.0g / cm 3 , melting point is 70℃ and glass transition temperature is -36℃.

[0074] Light calcium carbonate (G-1), weight average diameter is 6.5μm, bulk density is 0.56g / cm 3 , whiteness is 96% and moisture content is 0.4wt%.

[0075] Light calcium carbonate (G-2), weight average diameter is 20μm, bulk density is 0.75g / cm 3 , whiteness is 94wt% and moisture content is 0.4wt%.

[0076] Expandable microspheres (Q-1) were purchased from Crestron Technologies (Shanghai) Co., Ltd. with a brand name of DU608. The average particle diameter was 30 μm, and the average shell thickness of the expandable microspheres was 5 μm.

[0077] Expandable microspheres (Q-2) were purchased from Crestron Technologies (Shanghai) Co., Ltd. with a brand name of DU218. The average particle diameter was 25 μm, and the average shell thickness of the expandable microspheres was 5 μm.

[0078] Expandable microspheres (Q-3) were purchased from Crestron Technologies (Shanghai) Co., Ltd. with a brand name of DU1501M. The average particle diameter was 16 μm, and the average shell thickness of the expandable microspheres was 3 μm.

[0079] Titanium dioxide, weight average diameter is 2μm.

[0080] In the following examples, the relevant characteristic parameters are measured by the following methods:

[0081] (1) Tensile strength: tested in accordance with the requirements of GB 12592-2011.

[0082] (2) Elongation at break: Tested in accordance with the requirements of GB 12592-2011.

[0083] (3) Shore A hardness: Tested in accordance with the requirements of GB / T 2411-2008.

[0084] (4) Thermal conductivity: Tested in accordance with the requirements of GB / T 10294-2008.

[0085] (5) Waterproofness: Cut the sample in accordance with the provisions of GB 12592-2011, scratch the surface of the cut sample with a 0.1 mm deep and 20 mm long mark with a utility knife at the center of the circle, and then test in accordance with the provisions of GB 12592-2011.

[0086] In the following examples, the feeding speed of the parallel twin-screw extruder is 200 rpm, the aspect ratio is 44:1, and the filler is a combination of light calcium carbonate and titanium dioxide.

[0087] In the following examples, the plasticizer is dioctyl phthalate, the crosslinker is trimethylolpropane triacrylate, the lubricant is monoglyceride, the light stabilizer is N,N'-di(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, and the antioxidant is a combination of 1010 and 168.

[0088] In the following examples, 1 part by weight means 1 g.

[0089] Example 1

[0090] This example is used to illustrate the preparation of a polyvinyl chloride waterproofing membrane using the composition for polyvinyl chloride waterproofing membrane of the present invention according to the formula and process parameters in Table 1 and the following method, including:

[0091] (1) kneading the components in the composition for polyvinyl chloride waterproofing membrane to obtain a uniformly mixed mixture; wherein the specific operation of kneading is:

[0092] (S1) adding components such as polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, light calcium carbonate, crosslinking agent, antioxidant, titanium dioxide, calcium zinc stabilizer, lubricant and light stabilizer into a high-speed kneader for mixing and heating (end point temperature is 105° C., time is 15 min, speed is 110 rpm, to obtain an intermediate;

[0093] (S2) transferring the intermediate into a cold mixing kettle for cooling (end point temperature is 40° C.) under stirring at a speed of 45 rpm, and then contacting and mixing the obtained material with expandable microspheres for 5 minutes to obtain a uniformly mixed compound;

[0094] (2) The mixed materials are sequentially extruded and plasticized by a parallel twin-screw extruder, calendered and shaped by a three-roll calender, and irradiated and cross-linked by an electron accelerator device, and finally cut, coiled, packaged, and stored according to the specified size. Extrusion plasticization, calendering and shaping, and irradiation cross-linking.

[0095] Unless otherwise specified, the remaining examples are carried out using the same process as Example 1, except that the composition formula and process parameters of the polyvinyl chloride waterproof membrane used are different, see Table 1 for details.

[0096] Table 1

[0097]

[0098]

[0099] Table 1 (continued)

[0100]

[0101]

[0102] Test Case

[0103] The above-mentioned test method was used to measure the performance of the polyvinyl chloride waterproof membrane obtained in each example. The specific results are shown in Table 2.

[0104] Table 2

[0105]

[0106] From the above results, it can be seen that the polyvinyl chloride waterproof membrane prepared by the composition for polyvinyl chloride waterproof membrane provided by the present invention has low hardness and high toughness. At the same time, the waterproof membrane has good waterproof function while being able to insulate and heat-preserve. Its excellent performance can fully meet the requirements of various performance test indicators.

[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for polyvinyl chloride waterproofing membrane, characterized in that: The composition contains polyvinyl chloride, ethylene-vinyl acetate-carbon monoxide copolymer, plasticizer, filler, expandable microspheres, crosslinking agent, and antioxidant; Relative to 100 parts by weight of the polyvinyl chloride, the content of the ethylene-vinyl acetate-carbon monoxide copolymer is 10-40 parts by weight, the content of the plasticizer is 35-50 parts by weight, the content of the filler is 20-55 parts by weight, the content of the expandable microsphere is 1-3 parts by weight, the content of the cross-linking agent is 1-3 parts by weight, and the content of the antioxidant is 0.1-0.4 parts by weight; Wherein, the weight average molecular weight of the polyvinyl chloride is 150,000-210,000, and the average degree of polymerization is 1000-1350; The melting point of the ethylene-vinyl acetate-carbon monoxide copolymer is 45-66°C; The average particle diameter of the expandable microspheres is 20-50 μm; the expandable microspheres have a core-shell structure, and the average thickness of the shell of the expandable microspheres is 5-15 μm.

2. The composition according to claim 1, wherein The melt mass flow rate of the ethylene-vinyl acetate-carbon monoxide copolymer at 190° C. and a load of 2.16 kg is 25-35 g / 10 min, and the density is 1-1.02 g / cm 3 .

3. The composition according to claim 1, wherein The material forming the shell of the expandable microsphere includes a thermoplastic acrylic polymer.

4. The composition according to any one of claims 1 to 3, wherein The filler is light calcium carbonate and / or titanium dioxide; And / or, the content of the light calcium carbonate is 20-50 parts by weight, and the content of the titanium dioxide is 2-4 parts by weight; And / or, the weight average diameter of the light calcium carbonate is 2.6-18 μm, and the bulk density is 0.5-0.7 g / cm 3 ; And / or, the weight average diameter of the titanium dioxide is 2-3 μm.

5. The composition according to any one of claims 1 to 3, wherein The antioxidant is a combination of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a weight ratio of 1:1-2.

6. The composition according to any one of claims 1 to 3, wherein The composition further comprises at least one of a calcium zinc stabilizer, a lubricant and a light stabilizer; And / or, relative to 100 parts by weight of the polyvinyl chloride, the content of the calcium zinc stabilizer is 2-4 parts by weight, the content of the lubricant is 0.1-1 part by weight, and the content of the light stabilizer is 0.1-1 part by weight.

7. A method for preparing a polyvinyl chloride waterproofing membrane, characterized in that: The method comprises: kneading, extruding and plasticizing, calendering and shaping, and irradiating and crosslinking the components in the composition for polyvinyl chloride waterproofing coiled material in sequence; The composition for polyvinyl chloride waterproof membrane is the composition according to any one of claims 1 to 6.

8. The method according to claim 7, wherein: The extrusion plasticization conditions include: temperature of 140-180°C, extrusion speed of 3-6m / min; And / or, the conditions for radiation cross-linking include: irradiation energy of 1-2 MeV, beam current of 10-12 mA, and irradiation dose of 100-120 kGy.

9. The polyvinyl chloride waterproofing membrane prepared by the method according to claim 7 or 8.

10. Use of the polyvinyl chloride waterproofing membrane according to claim 9 in the field of building waterproofing.

Citation Information

Patent Citations

  • Environment-friendly cross-linked polyvinyl chloride waterproof coiled material and preparation method thereof

    CN108690290A

  • Inner reinforced aging-resistant polyvinyl chloride waterproof coiled material and preparation method thereof

    CN110983808A

  • Composition with improved low-temperature flexibility and elasticity

    CN101613508A

  • Plasticized polyvinyl chloride material and preparation method thereof

    CN103965564A

Cited By

  • Anti-seepage high-extension PVC coiled material for swimming pool and preparation method of anti-seepage high-extension PVC coiled material

    CN120349601A

  • A high-ductility PVC coiled material for swimming pools and a preparation method thereof

    CN120349601B